2015
DOI: 10.1007/s12035-015-9583-6
|View full text |Cite
|
Sign up to set email alerts
|

bFGF Protects Against Blood-Brain Barrier Damage Through Junction Protein Regulation via PI3K-Akt-Rac1 Pathway Following Traumatic Brain Injury

Abstract: Many traumatic brain injury (TBI) survivors sustain neurological disability and cognitive impairments due to the lack of defined therapies to reduce TBI-induced blood-brain barrier (BBB) breakdown. Exogenous basic fibroblast growth factor (bFGF) has been shown to have neuroprotective function in brain injury. The present study therefore investigates the beneficial effects of bFGF on the BBB after TBI and the underlying mechanisms. In this study, we demonstrate that bFGF reduces neurofunctional deficits and pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
80
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 116 publications
(86 citation statements)
references
References 39 publications
6
80
0
Order By: Relevance
“…Animal care and all animal experiments conformed to the Guide for the Care and Use of Laboratory Animals provided by U.S. National Institutes of Health and were approved by the Animal Care and Use Committee of Wenzhou Medical College, China. The controlled cortical impact (CCI) mouse traumatic brain injury (TBI) model was constructed by surgical procedures as previously described . Briefly, C57BL/6J (20–25 g) mice were anesthetized with 4% choral hydrate (10 mL kg −1 intraperitoneally [IP]) and surgery was performed under aseptic conditions and mounted in a stereotaxic system (Benchmark Deluxe; MyNeurolab, St Louis, MO, USA).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Animal care and all animal experiments conformed to the Guide for the Care and Use of Laboratory Animals provided by U.S. National Institutes of Health and were approved by the Animal Care and Use Committee of Wenzhou Medical College, China. The controlled cortical impact (CCI) mouse traumatic brain injury (TBI) model was constructed by surgical procedures as previously described . Briefly, C57BL/6J (20–25 g) mice were anesthetized with 4% choral hydrate (10 mL kg −1 intraperitoneally [IP]) and surgery was performed under aseptic conditions and mounted in a stereotaxic system (Benchmark Deluxe; MyNeurolab, St Louis, MO, USA).…”
Section: Methodsmentioning
confidence: 99%
“…A dose of 500 µg kg −1 FGF2 C78S/C96S , PEG‐FGF2 C78 , and PEG‐FGF2 C96 was administrated intranasally 1 h before TBI induction in the TBI+FGF2 C78S/C96S , TBI+PEG‐FGF2 C78 , and TBI+PEG‐FGF2 C96 groups, respectively. The dosage and mode of administration were selected based on a previous report …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…31 BBB breakdown occurs within hours or days after TBI accompanying with oedema, neuroinflammation and cell death. 33 Dl-NBP is widely used to treat for ischaemic stroke patients. 33 Dl-NBP is widely used to treat for ischaemic stroke patients.…”
Section: Discussionmentioning
confidence: 99%
“…One common component in several shear-mediated signaling pathways involves the activation of small GTPases8, 15. One small GTPase in particular, RhoA, is also implicated as a regulator of BBB integrity16- 19. Previous studies have demonstrated that increased RhoA activity leads to a disassembly of the complexes within cell-cell junctions and subsequent barrier disruption8, 20, 21. Another small GTPase, Rac1, has been associated with stabilization of the BBB22, 23, and recent studies have also identified Rac1 activation as a downstream response to fluid shear stress12. Therefore, this study investigates the effect of shear stress on the activity of both RhoA and Rac1 to gain insight into their role in shear-mediated barrier integrity.…”
Section: Introductionmentioning
confidence: 99%